Towards sustainable multi-bed hospital wards: numerical evaluation of infection control, thermal comfort, and energy savings under real-world ventilation strategies - Mei Yan Chong; Hui An; Brenda Sze Peng Ang; Chew Beng Soh; Szu-Cheng Chien; Peng Cheng Wang; Simon Ching Man Yu (Energy and Buildings, 2026)

Interfacial electron redistribution and tandem active sites enable enhanced nitrate to ammonia conversion in Zr-MOF/MoS2 heterostructures - Naveen Karuppusamy; Zi-Yan Zhan; Ruspika Sundaresan; Chun Hsien Wu; Pandiyarajan Anand; Jeyakumar Karthikeyan; Hsu-Feng Lee; Hung-Pin Hsu; Yu-Cheng Shao; Yi-Ping Wang; Ching-Wei Tung (Chemical Engineering Journal, 2026)

Targeting microglial TLR3–NF-κB/MAPK and JAK/STAT Axis: PEITC as a suppressor of poly (I:C)-induced neuroinflammation - Yi-Ching Lan; Yan-Ru Xiao; Yow-Wen Hsieh; Yih-Dih Cheng; Shu-Fen Peng; Fu-Shin Chueh; Hsu-Tung Lee; Yu-Sheng Hsieh; Wei-Cheng Jiang; Wen-Tsong Hsieh; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

Finite strain pattern inferred from magnetic fabrics across the southern portion of the Central Range, Taiwan - Ya-Chu Tseng; En-Chao Yeh; Ning-Shan Hui; Yu-Min Chou; Jian-Cheng Lee; Ching-Chou Fu (Tectonophysics, 2026)

Probabilistic seismic hazard assessment for Taiwan: Updates and improvements in TEM PSHA2025 - Jia-Cian Gao; Jo-Chen Kao; Chung-Han Chan; Ray Y. Chuang; Cheng-Hung Chen; J. Bruce H. Shyu; Kuo-En Ching; Yu Wang; Kuo-Fong Ma (Engineering Geology, 2026)

Correction: Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Anticancer Bioactive Peptides from Plants: Sources, Action Mechanisms, and Potential Superiority to Conventional Chemotherapy - Mao-Cheng Sun; Shi-Qi Yu; Changhui Zhao; Chi-Ching Lee; Itthanan Suttikhana; Tolulope Joshua Ashaolu (Probiotics and Antimicrobial Proteins, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Empagliflozin attenuates sorafenib-promoted renal ferroptosis and inflammation by targeting cyclooxygenase-2/prostaglandin E2 axis - Ming-Kai Tsai; Wen-Chin Lee; Shih-Chung Huang; Chao-Cheng Huang; Yi-Chen Wang; Chien-Han Yuan; Chih-Chiang Wang; Ching-Han Liu; Nan-Chieh Huang; Yi-Chen Chang; Cheng-Chieh Fang; Bi-Wen Yeh; et al. (Toxicology and Applied Pharmacology, 2025)

The influence of trees shade level on human thermal comfort and the development of applied assessment tools - Yu-Ying Wei; Ching-Yin Cheng; Tzu-Ping Lin (Landscape and Urban Planning, 2025)

Anti-cancer effect of Willughbeia edulis Roxb. Stem extract in hepatocellular carcinoma cells through triggering apoptosis and G2/M cell cycle arrest - Thi Tuyet Nhung Nguyen; Yu-Chi Lin; Ching-Kuo Lee; Jing-Jy Cheng (Phytochemistry Letters, 2025)

Reducing melamine exposure and oxidative stress markers in melamine-exposed workers: A pragmatic intervention study - Chia-Fang Wu; Chih-Hong Pan; Yu-Ming Hsu; Chiung-Yu Peng; Ching-Mei Cheng; Sih-Syuan Li; Chien-Ping Huang; Ming-Tsang Wu (Journal of Hazardous Materials, 2025)

Accuracy of volume equations in innovative egg-shaped calculations: Using shape functions to enhance compensation coefficients - Ching-Wei Cheng; Ko-Jung Huang; Yu-Kai Weng; Ping-Kun Tsai; Chia-Chun Lai (Biosystems Engineering, 2025)

Enhanced Hair Growth Through Transdermal Delivery of Bacopa Monnieri Extract Using a Needle-Free Supersonic Atomizer - Yu-Chiuan Wu; Yi-Ping Lin; Ching-Yi Chang; Hsia-Ying Cheng; Tien-Huei Chu; Chien-Chih Chen; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2025)

Polycyclic aromatic hydrocarbon-aryl hydrocarbon receptor signaling regulates chronic inflammation in lung-gut axis - Tzu-Yu Cheng; Ching-Shan Luo; Po-Hao Feng; Kuan-Yuan Chen; Chih-Cheng Chang; Nguyen Van Hiep; Yueh-His Chen; Yun-Kai Yeh; Sheng-Ming Wu (Toxicology and Applied Pharmacology, 2025)

Microplastic-induced hypertension in rats: A two-hit model exploring oxidative stress and gut microbiota - Yu-Chun Cheng; Wei-Ling Chen; Hong-Ren Yu; Ching-Yi Tsai; Jiunn-Ming Sheen; Mao-Meng Tiao; Chien-Ning Hsu; You-Lin Tain (NanoImpact, 2025)

The significance of the high-amplitude magnetic anomaly belt in the seismotectonics of mid-west Taiwan - Wen-Bin Doo; Yin-Sheng Huang; Wen-Nan Wu; Ching-Yu Cheng; Chung-Liang Lo; Hsueh-Fen Wang; Shiou-Ya Wang; Yin-Tung Yen (Journal of Asian Earth Sciences, 2025)

A potential closed-loop reutilization of iron sludge for wastewater treatment through the solid state reaction with spent coffee grounds - Kun Qin; TsingHai Wang; Wei-Tong Li; Zi-Ying Lu; Cheng-Yu Li; Wei-Fan Kuan; Jenn-Fang Su; Ching-Lung Chen (Process Safety and Environmental Protection, 2025)

Fabrication of sesamin-loaded sodium caseinate nanoparticles: Insight to characterization, in vitro digestion, and molecular docking analysis - Wan-Yi Liu; Tzu-Yu Chen; Yun-Shan Hsieh; Yung-Yi Cheng; Shiou-Ling Li; Li-Ching Chang; Yu-Tse Wu (Food Bioscience, 2025)

Pixel array-based urine biosensor for detection of trimethylamine N-oxide and glucose for early detection of diabetic kidney disease - Mei-Ching Yu; Chi-Jen Lo; Wei-Cheng Lin; Wei-Lun Yen; Yun-Yu Hsieh; Bing-Hong Chen; Fu-Sung Lo (Analytica Chimica Acta, 2025)

Vision transformer-based stratification of pre/diabetic and pre/hypertensive patients from retinal photographs for 3PM applications - Krithi Pushpanathan; Yang Bai; Xiaofeng Lei; Jocelyn Hui Lin Goh; Can Can Xue; Samantha Min Er Yew; Miaoli Chee; Ten Cheer Quek; Qingsheng Peng; Zhi Da Soh; Marco Chak Yan Yu; Jun Zhou; et al. (EPMA Journal, 2025)
Objective Diabetes and hypertension pose significant health risks, especially when poorly managed. Retinal evaluation though fundus photography can provide non-invasive assessment of these diseases, yet prior studies focused on disease presence, overlooking control statuses. This study evaluated vision transformer (ViT)-based models for assessing the presence and control statuses of diabetes and hypertension from retinal images. Methods ViT-based models with ResNet-50 for patch projection were trained on images from the UK Biobank ( n = 113,713) and Singapore Epidemiology of Eye Diseases study ( n = 17,783), and externally validated on the Singapore Prospective Study Programme ( n = 7,793) and the Beijing Eye Study ( n = 6064). Model performance was evaluated using the area under the receiver operating characteristic curve (AUROC) for multiple tasks: detecting disease, identifying poorly controlled and well-controlled cases, distinguishing between poorly and well-controlled cases, and detecting pre-diabetes or pre-hypertension. Results The models demonstrated strong performance in detecting disease presence, with AUROC values of 0.820 for diabetes and 0.781 for hypertension in internal testing. External validation showed AUROCs ranging from 0.635 to 0.755 for diabetes, and 0.727 to 0.832 for hypertension. For identifying poorly controlled cases, the performance remained high with AUROCs of 0.871 (internal) and 0.655–0.851 (external) for diabetes, and 0.853 (internal) and 0.792–0.915 (external) for hypertension. Detection of well-controlled cases also yielded promising results for diabetes (0.802 [internal]; 0.675–0.838 [external]), and hypertension (0.740 [internal] and 0.675–0.807 [external]). In distinguishing between poorly and well-controlled disease, AUROCs were more modest with 0.630 (internal) and 0.512–0.547 (external) for diabetes, and 0.651 (internal) and 0.639–0.683 (external) for hypertension. For pre-disease detection, the models achieved AUROCs of 0.746 (internal) and 0.523–0.590 (external) for pre-diabetes, and 0.669 (internal) and 0.645–0.679 (external) for pre-hypertension. Conclusion ViT-based models show promise in classifying the presence and control statuses of diabetes and hypertension from retinal images. These findings support the potential of retinal imaging as a tool in primary care for opportunistic detection of diabetes and hypertension, risk stratification, and individualised treatment planning. Further validation in diverse clinical settings is warranted to confirm practical utility.

BTEX exposure and metabolite levels in Taiwan schoolchildren near petrochemical areas - Wei-shan Chin; Ching-chun Huang; Yu-cheng Chen; Jing-fang Hsu; Chih-Da Wu; Pinpin Lin; Pau-chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

ONC201 exerts oncogenic effects beyond its mitochondria-disturbing role in neuroblastoma subsets - Jyun-Hong Jiang; Yu-Han Lin; Pei-Lin Liao; Ting-Ya Chen; Hui-Ching Chuang; Chao-Cheng Huang; Wen-Ming Hsu; Jiin-Haur Chuang; Wei-Shiung Lian (Journal of Molecular Medicine, 2025)
Neuroblastoma (NB) is a formidable challenge in pediatric oncology due to its intricate molecular landscape, necessitating multifaceted therapeutic approaches. ONC201 is an imipridone antibiotic compound with a promising drug candidate leveraging its potent anticancer properties against the mitochondrial proteases ClpP and ClpX. Despite demonstrating early clinical promise, particularly in MYCN -amplified NB, its efficacy in non- MYCN -amplified NB remains a subject worthy of investigation. In this study, we extended the coverage of ONC201 to treat non- MYCN -amplified NB, and our data implicated ONC201’s inability to reduce tumor growth in animal models harboring SK-N-AS or SK-N-FI cell lines. Interestingly, ONC201 induced the expression of oncogenic markers c-Myc and LGR5 while downregulating the tumor suppressor ATRX. While it fails to attenuate tumor neovascularization in non- MYCN -amplified NB xenografts, its effectiveness differs from that of its MYCN-amplified counterpart. Rho zero (ρ0)-SK-N-AS cells treated with ONC201 showed comparable observed trends in parental SK-N-AS cells, including LGR5 upregulation and ATRX downregulation, suggesting that ONC201’s multifaceted actions extend beyond mitochondrial targets. Our elucidation highlights the need to discern molecular signatures when deploying ONC201 monotherapy against NB, which lacks MYCN- amplification.

4-Anilinoquinolinylchalcone derivatives mediate antifibrotic effects through ERK/MRTF—a signaling pathway crosstalk - Padhmavathi Selvam; Chih Hua Tseng; Ching Tung Wang; Yu-Yo Sun; Yeh-Long Chen; Yu-Tse Kao; Hans-Uwe Dahms; Chih Mei Cheng (Environmental Science and Pollution Research, 2025)

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Ambient stable ZnBr2-assisted lead-free perovskite for enhanced piezoelectricity of polyvinylidene fluoride in versatile piezo-phototronic applications - Manikandan Venkatesan; Wei-Chun Lin; Wei-Cheng Chen; Jayashree Chandrasekar; Yu-Hang Huang; Kai-Wei Lin; Zih-Syuan Syu; Ja-Hon Lin; Wei-Hung Chiang; Wei-Ren Liu; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

Multiscale modelling and infection probability of SARS-CoV-2 transmission in a typical lecture theatre - Mei Yan Chong; Hui An; Peng Cheng Wang; Chew Beng Soh; Szu-Cheng Chien; Edward Reuben Roch; Jun Jie Koh; Simon Ching Man Yu (Building and Environment, 2025)

Using Gaussian Mixture Model Clustering for the Automated Segmentation of Cerebral Arteriovenous Malformations in Magnetic Resonance Images - Ting-Yu Lin; Cheng‑Chia Lee; Yu-Wei Chen; Hsiu-Mei Wu; Ching-Jen Chen; Huai-Che Yang; Syu-Jyun Peng (Journal of Medical and Biological Engineering, 2025)

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Application of Computational Fluid Dynamics and Semi-Empirical Speed Loss Prediction for Weather Routing - Chih-Wen Cheng; Yu-An Tzeng; Ming-Hsiung Chang; Shang-Chi Liu; Ho-King Cheung; Ching-Yeh Hsin (Journal of Marine Science and Engineering, 2024)
This study presents an optimized system for ship route planning. Computational fluid dynamics simulations were used to modify Kwon’s semi-empirical speed loss estimation method, enabling efficient route planning under variable sea conditions. The study focused on improving the prediction of speed loss in irregular waves for container ships and further applying this to ship-optimized voyage planning. Dynamic programming was used for optimized voyage planning by modifying the ship course in response to meteorological data; this approach could balance both energy efficiency and safety. The modified speed loss predictions aligned closely with the simulation results, enhancing the reliability of weather routing decisions. Case studies for trans-Pacific and trans-Atlantic voyages demonstrated that the proposed system could significantly reduce the voyage time. These findings highlight the potential of real-time updates in voyage planning. The proposed system is a valuable tool for captains and fleet managers. The applicability of this system can be further broadened by validating it on different ship types.

Nanoplastics indirectly compromise lettuce growth in hydroponic systems via microbial extracellular vesicles derived from Curvibacter fontanus - Bao-Hong Lee; Yi-Ching Lin; Yu-Juan Zheng; Tang-Long Shen; Ting-Yu Cheng; Chih-Chia Huang; Wei-Hsuan Hsu (Journal of Hazardous Materials, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Effect of a tropical cyclone on the pelagic ecosystem of a continental shelf - Chung‐Chi Chen; Chih‐hao Hsieh; Yu‐Hsin Cheng; Wei‐Jen Huang; Wen‐Chen Chou; Fuh‐Kwo Shiah; Gwo‐Ching Gong; Tzong‐Yueh Chen (Limnology and Oceanography, 2024)
This study aimed to comprehend the effects of Typhoon Maria on the pelagic ecosystem in the southern East China Sea. Shipboard measurements were conducted at eight sampling stations before (2–4 d) and after (3–6 d) the typhoon, which enabled the evaluation of the potential impacts of the typhoon on this pelagic ecosystem, with particular focus on carbon dynamics. Following the typhoon's passage, there was a slight drop in sea surface temperature. The response of the variables to the typhoon, however, exhibited variations at different sampling stations. For further analysis, t ‐tests compared variables, while type II regression assessed the linear correlation between two variables. Overall, during the post‐typhoon period, concentrations of nitrate, chlorophyll a , primary production, bacterial biomass and production, plankton community respiration, and abundance of large phytoplankton (> 2 μ m) and the relative abundance of picophytoplankton among larger‐sized picoeukaryotes were higher compared to the pre‐typhoon period. The mean value of fugacity of CO 2 was similar to or slightly lower than pre‐typhoon period. Although the typhoon‐induced vigorous primary production might have absorbed a significant amount of CO 2 , the decrease in fugacity of CO 2 could have been offset by the plankton community respiration. The findings suggest that the typhoon enhanced physical disturbance and increased water column mixing, which, in turn, augmented nutrient availability and promoted plankton growth in the shallow water column. Overall, this study sheds light on the complex interactions between typhoons and marine ecosystems and highlights the importance of further investigating these phenomena to better understand their ecological implications.

Unraveling the alternative process configurations for more environmentally friendly Maleic Anhydride production - Ting-Yu Yu; Ching-Tai Kuo; Cheng-Kai Lai; Wangyun Won; Bor-Yih Yu (Process Safety and Environmental Protection, 2024)

Maintaining KEAP1 levels in retinal pigment epithelial cells preserves their viability during prolonged exposure to artificial blue light - Ching-Hao Li; Tsung-Min Yang; Ida Fitriana; Te-Chao Fang; Liang-Huan Wu; George Hsiao; Yu-Wen Cheng (Journal of Photochemistry and Photobiology B: Biology, 2024)

Development of fermented Atemoya (Annona cherimola × Annona squamosa)-Amazake increased intestinal next-generation probiotics - Yeu-Ching Shi; She-Ching Wu; Yi-Ching Lin; Yu-Juan Zheng; Cheng-Hao Huang; Bao-Hong Lee (Food Chemistry, 2024)

A negative regulatory role of β-cell-derived exosomes in the glucose-stimulated insulin secretion of recipient β-cells - Chia-Ching Yu; Ching-Yao Yang; Ting-Yu Chang; Kuo-Cheng Lan; Shing-Hwa Liu (Archives of Toxicology, 2024)

Development of Quantitative Norms for Normal Lung Uptake Based on Three-Dimensional Gallium-67 Single Photon Emission Computed Tomography/Computed Tomography - Tzyy-Ling Chuang; Wei-Lin Li; Yu-Ching Hs; Jyh-Cheng Chen; Yuh-Feng Wang (Journal of Medical and Biological Engineering, 2024)
Purpose Gallium-67 (Ga-67) lung scans assess alveolitis and interstitial lung disease, with Ga-67 accumulation correlating with inflammation intensity as seen in lung biopsy sections. Both semi-quantitative and quantitative methods have been used, with the latter providing an inflammatory activity index linked to lung lavage and histopathological scores. However, differing reference points result in varying outcomes. This study aimed to establish standard Ga-67 index parameters using semi-quantitative analysis and a linear regression model based on planar and SPECT/CT images. Methods Twenty subjects without lung disease received a 5–6 mCi Ga-67 injection via the ankle. Both planar and SPECT/CT images were analyzed, with semi-quantitative values assessed using GraphPad Prism 9.5.1. Results Compared to planar images, SPECT/CT acquisitions for the lung-to-arm uptake ratio proved the most reliable indicator for assessing lung inflammation. Increased lung Ga-67 uptake was defined as greater than 2 standard deviations from the average Ga-67 uptake for healthy subjects. The normal range was 0.065 ± 0.049 for the right side and 0.076 ± 0.070 for the left side. Conclusion Lung-to-arm ratios in SPECT/CT images are more accurate than those in planar images. This method should be adopted as a standard clinical practice, providing more reliable diagnostic information and improving patient management. Future studies should compare patients without lung disease to those with lung disease to determine the diagnostic benefit of these norms.

Detachable acoustofluidic droplet-sorter - Dhrubajyoti Das; Shih-Hong Huang; Choa-Li Weng; Chien-Hung Yu; Chao-Kai Hsu; Yung-Chun Lee; Hui-Ching Cheng; Han-Sheng Chuang (Analytica Chimica Acta, 2024)

Organic light-emitting diode therapy promotes longevity through the upregulation of SIRT1 in senescence-accelerated mouse prone 8 mice - Yue-Hua Deng; Chi-Sheng Chiou; Ching-Yu Tsai; Abhinay Kumar Singh; Edlin Anahi Pelaze Achtmann; Bou-Yue Peng; Tommy Yet-Min Lin; Hsin-Chung Cheng; Pao-Chang Chiang; Win-Ping Deng (Journal of Photochemistry and Photobiology B: Biology, 2024)

Predicting ischemic stroke patients’ prognosis changes using machine learning in a nationwide stroke registry - Ching-Heng Lin; Yi-An Chen; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Wei-Lun Chang; Yang C. Fann; Kai-Cheng Hsu; Jiunn-Tay Lee (Medical & Biological Engineering & Computing, 2024)
Accurately predicting the prognosis of ischemic stroke patients after discharge is crucial for physicians to plan for long-term health care. Although previous studies have demonstrated that machine learning (ML) shows reasonably accurate stroke outcome predictions with limited datasets, to identify specific clinical features associated with prognosis changes after stroke that could aid physicians and patients in devising improved recovery care plans have been challenging. This study aimed to overcome these gaps by utilizing a large national stroke registry database to assess various prediction models that estimate how patients’ prognosis changes over time with associated clinical factors. To properly evaluate the best predictive approaches currently available and avoid prejudice, this study employed three different prognosis prediction models including a statistical logistic regression model, commonly used clinical-based scores, and a latest high-performance ML-based XGBoost model. The study revealed that the XGBoost model outperformed other two traditional models, achieving an AUROC of 0.929 in predicting the prognosis changes of stroke patients followed for 3 months. In addition, the XGBoost model maintained remarkably high precision even when using only selected 20 most relevant clinical features compared to full clinical datasets used in the study. These selected features closely correlated with significant changes in clinical outcomes for stroke patients and showed to be effective for predicting prognosis changes after discharge, allowing physicians to make optimal decisions regarding their patients’ recovery. Graphical Abstract

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Pioneering molecularly-level Fe sites immobilized on graphene quantum dots as a key activity descriptor in achieving highly efficient oxygen evolution reaction - Mia Rinawati; Ling-Yu Chang; Chia-Yu Chang; Ching-Cheng Chang; Darwin Kurniawan; Wei-Hung Chiang; Wei-Nien Su; Brian Yuliarto; Wei-Hsiang Huang; Min-Hsin Yeh (Chemical Engineering Journal, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

Nucleocytoplasmic shuttling of BEFV M protein-modulated by lamin A/C and chromosome maintenance region 1 through a transcription-, carrier- and energy-dependent pathway - Yu-Kang Chang; Yi-Jyum Lin; Ching-Yuan Cheng; Pei-Chien Tsai; Chi-Young Wang; Brent L. Nielsen; Hung-Jen Liu (Veterinary Microbiology, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Exposure estimates of PM2.5 using the land-use regression with machine learning and microenvironmental exposure models for elders: Validation and comparison - Chin-Yu Hsu; Wei-Ting Hsu; Ching-Yi Mou; Pei-Yi Wong; Chih-Da Wu; Yu-Cheng Chen (Atmospheric Environment, 2024)

Green cost performance measure of China’s thermal power industry: evidence from Chinese 30 provinces - Xiang Chen; Jiayu Zhang; Chih-Yu Yang; Ching-Cheng Lu; Jun Wang (Environment, Development and Sustainability, 2024)

A longitudinal study on the change in sleep across three waves of the COVID-19 outbreaks in Hong Kong - Denise Shuk Ting Cheung; Branda Yee-Man Yu; Simon Ching Lam; Doris Yin Ping Leung; Ka-Fai Chung; Fiona Yan-Yee Ho; Shu-Cheng Chen; Wing-Fai Yeung (Sleep and Biological Rhythms, 2024)

Outcome-Based blind tests for leakage diagnosis in underground watermains by acoustic technologies - Wallace Wai-Lok Lai; Tom Chun-Wai Lau; Alex Yu-Ching Cheng; Panda Kai-Chun Liu; Joseph Wang-Chi Leung (Tunnelling and Underground Space Technology, 2023)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Tandem surface engineering of graphene quantum dot-assisted fluorinated NiFe Prussian blue analogue for electrocatalytic oxygen evolution reaction - Angelina Melanita Tarigan; Sofiannisa Aulia; Mia Rinawati; Ling-Yu Chang; Yao-Sheng Cheng; Ching-Cheng Chang; Wei-Hsiang Huang; Jeng-Lung Chen; Heru Setyawan; Min-Hsin Yeh (Chemical Engineering Journal, 2023)

Corrigendum to “PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet” [Toxicology and Applied Pharmacology, 470, (2023), 116557] - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

Severity of Liver Cirrhosis Evaluated by Digital Subtraction Angiography Using Quantitative Color-Coding Analysis Before Transarterial Embolization - Lung-Hui Giiang; Chang-Hsien Liu; Chih-Yung Yu; Te-Pao Lin; Hsiang-Cheng Chen; Chun-Jung Juan; Yu-Ching Chou (Journal of Medical and Biological Engineering, 2023)

A concise chemoenzymatic total synthesis of neutral Globo-series glycosphingolipids Globo A and Globo B, and Forssman and para-Forssman antigens - Yu-Ching Chiang; Chun-Yen Wu; Pei-Yun Chiang; Avijit K. Adak; Chun-Cheng Lin (Glycoconjugate Journal, 2023)

Minimal addition of transglutaminase on the preparation and characteristics of tilapia (Oreochromis mossambicus) surimi - Ping-Hsiu Huang; Yu-Tsung Cheng; Yung-Jia Chan; Wen-Chien Lu; Wen-Ching Ko; Hung-Chun Hsieh; Po-Hsien Li (Fisheries Science, 2023)

Dynamic total factors’ environmental efficiency in European union countries - Ching-Cheng Lu; Yung-ho Chiu; I-Fang Lin; Tai-Yu Lin (Environment, Development and Sustainability, 2023)

PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Bioremediation potential of cadmium by recombinant Escherichia coli surface expressing metallothionein MTT5 from Tetrahymena thermophila - Che-Wei Lu; Hsin-Cheng Ho; Chao-Ling Yao; Tsung-Yu Tseng; Chih-Ming Kao; Ssu-Ching Chen (Chemosphere, 2023)

Association between cold weather, influenza infection, and asthma exacerbation in adults in Hong Kong - Xi Xiong; Yuchen Wei; Holly Ching Yu Lam; Carlos King Ho Wong; Steven Yuk Fai Lau; Shi Zhao; Jinjun Ran; Conglu Li; Xiaoting Jiang; Qianying Yue; Wei Cheng; Huwen Wang; et al. (Science of The Total Environment, 2023)

Two-stage dynamic data envelopment analysis measuring the overall efficiency and productivity changes of industry and agriculture in EU countries - Ching-Cheng Lu; I-Fang Lin; Tai-Yu Lin; Yung-ho Chiu (Journal of Cleaner Production, 2023)

Development of the dried blood spot preparation protocol for comprehensive evaluation of the hematocrit effect - Chih-Ning Cheng; Yu-Fong Peng; Ju-Yu Chen; Guan-Yuan Chen; Te-I Weng; Ching-Hua Kuo (Analytica Chimica Acta, 2023)

Predictive, preventive, and personalized management of retinal fluid via computer-aided detection app for optical coherence tomography scans - Ten Cheer Quek; Kengo Takahashi; Hyun Goo Kang; Sahil Thakur; Mihir Deshmukh; Rachel Marjorie Wei Wen Tseng; Helen Nguyen; Yih-Chung Tham; Tyler Hyungtaek Rim; Sung Soo Kim; Yasuo Yanagi; Gerald Liew; et al. (EPMA Journal, 2022)

Lactobacillus plantarum PS128 Promotes Intestinal Motility, Mucin Production, and Serotonin Signaling in Mice - Chih-Ming Chen; Chien-Chen Wu; Chin-Lin Huang; Min-Yu Chang; Shih-Hsuan Cheng; Ching-Ting Lin; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2022)
Lactobacillus plantarum PS128 has been reported as a psychobiotic to improve mental health through the gut–brain axis in experimental animal models. To explore its mechanism of action in the gut, this study aimed to analyze the effects of L. plantarum PS128 ingestion on naïve and loperamide (Lop)-induced constipation mice. We found that, in the two mouse models, the weight, number, and water content of feces in the L. plantarum PS128 group were higher than those in the vehicle control group. Histological observation revealed that L. plantarum PS128 increased the level of colonic mucins including the major mucin MUC2. In addition, the charcoal meal test showed that L. plantarum PS128 significantly increased the small intestine transit in naïve mice, but not in the Lop-treated mice. Since intestinal serotonin has been found to modulate motility, we further analyzed the expression of genes related to serotonin signal transduction in the small intestine of naïve mice. The results showed that L. plantarum PS128 significantly altered the expression levels of Tph1 , Chga , Slc6a4 , and Htr4 , but did not affect the expression levels of Tph2 , Htr3a , and Maoa . Furthermore, immunohistochemistry revealed that L. plantarum PS128 significantly increased the number of serotonin-containing intestinal cells in mice. Taken together, our results suggest that L. plantarum PS128 could promote intestinal motility, mucin production, and serotonin signal transduction, leading to a laxative effect in mice.

Geographic distance, sedimentation, and substrate shape cryptic crustose coralline algal assemblages in the world’s largest subtropical intertidal algal reef - Shing Hei Zhan; Ling Chen; Chen‐Pan Liao; Wun‐Ruei Chang; Cheng‐Chin Li; Guang‐You Tang; Ching‐Yu Liou; Wei‐Lung Wang; Shih‐Wei Wang; Shao‐Lun Liu (Molecular Ecology, 2022)
Algal reefs, concreted by crustose coralline algae (CCA), are the main biotic reefs in temperate waters but rare in the subtropics and tropics. The world's largest known intertidal algal reef in the subtropics is the Taoyuan Algal Reef (TAR) located in the northwestern coast of Taiwan. The biodiversity and ecology of the TAR are scarcely explored, and now the reef is imperiled by industrialization. Here, we document cryptic species of CCA in Taiwan, particularly the TAR, by sequencing the psb A genes of over 1800 specimens collected across Taiwan. We also examine the ecological background of the TAR by surveying its benthic composition and measuring its environmental parameters. Our data reveal that the TAR harbours a high diversity of cryptic CCA species (27 molecular operational taxonomic units, or mOTUs), many of which are potentially new to science (18 mOTUs) and/or endemic to the TAR (9 mOTUs). Comparing the CCA species inventory of the TAR with the rest of Taiwan shows that the TAR represents a unique hotspot of CCA taxa in the waters of Taiwan. Our analyses show that variation in the CCA assemblages in the TAR is associated with geographic distance, sedimentation, and substrate type (for example, reef vs. hermit crab shell), suggesting that dispersal limitation and contemporary environmental selection shape the CCA assemblages in the TAR. The data from this study can inform the monitoring of human impacts on the health of the TAR and contribute to our understanding of the ecological processes underlying algal reef development.

Interleukin-6 transiently promotes proliferation of osteoclast precursors and stimulates the production of inflammatory mediators - Peng-Yuan Chang; Hung-Kang Wu; Yu-Hsu Chen; Yu-Pao Hsu; Ming-Te Cheng; Ching-Hsiao Yu; Shau-Kwaun Chen (Molecular Biology Reports, 2022)

A Unique Diel Pattern in Carbonate Chemistry in the Seagrass Meadows of Dongsha Island: The Enhancement of Metabolic Carbonate Dissolution in a Semienclosed Lagoon - Wen-Chen Chou; Lan-Feng Fan; Chang-Chang Yang; Ying-Hsuan Chen; Chin-Chang Hung; Wei-Jen Huang; Yung-Yen Shih; Keryea Soong; Hsiao-Chun Tseng; Gwo-Ching Gong; Hung-Yu Chen; Cheng-Kuan Su (Frontiers in Marine Science, 2021)
In contrast to other seagrass meadows where seawater carbonate chemistry generally shows strong diel variations with higher pH but lower partial pressure of CO 2 ( p CO 2 ) during the daytime and lower pH but higher p CO 2 during nighttime due to the alternation in photosynthesis and respiration, the seagrass meadows of the inner lagoon (IL) on Dongsha Island had a unique diel pattern with extremely high pH and low p CO 2 across a diel cycle. We suggest that this distinct diel pattern in pH and p CO 2 could be associated with the enhancement of total alkalinity (TA) production coupled to carbonate sediment dissolution in a semienclosed lagoon. The confinement of the IL may hamper water exchange and seagrass detritus export to the adjacent open ocean, which may result in higher organic matter loading to the sediments, and longer residence time of the water in the IL, accompanied by microbial respiration (both aerobic and anaerobic) that may reduce carbonate saturation level to drive carbonate dissolution and thus TA elevation, thereby forming such a unique diel pattern in carbonate chemistry. This finding further highlights the importance of considering TA production through metabolic carbonate dissolution when evaluating the potential of coastal blue carbon ecosystems to buffer ocean acidification and to absorb atmospheric CO 2 , in particular in a semienclosed setting.

Evaluating the energy, health efficiency, and productivity in OECD - Ching-Cheng Lu; Yung-ho Chiu; Chih-Yu Yang; Tai-Yu Lin (Environmental Geochemistry and Health, 2021)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

Effect of selected sampling media, flow rate, and time on the sampling efficiency of a liquid impinger packed with glass beads for the collection of airborne viruses - Yen-Chi Chen; I-Jen Wang; Chih-Ching Cheng; Yu-Chiao Wu; Chun-Hsuan Bai; Kuo-Pin Yu (Aerobiologia, 2021)

Carbon monoxide-triggered health effects: the important role of the inflammasome and its possible crosstalk with autophagy and exosomes - Rong-Jane Chen; Yu-Hsuan Lee; Tzu-Hao Chen; Yu-Ying Chen; Ya-Ling Yeh; Ching-Ping Chang; Chien-Cheng Huang; How-Ran Guo; Ying-Jan Wang (Archives of Toxicology, 2021)

Risk of incident gastroesophageal reflux disease (GERD) in patients with sleep disorders: a population-based cohort study - Yu-Hsien Cheng; Tao-Hsin Tung; Pei-En Chen; Ching-Yao Tsai (Sleep and Biological Rhythms, 2021)

New land use regression model to estimate atmospheric temperature and heat island intensity in Taiwan - Chin-Yu Hsu; Uen-Ching Ng; Chiao-Ying Chen; Yu-Cheng Chen; Mu-Jean Chen; Nai-Tzu Chen; Shih-Chun Candice Lung; Huey-Jen Su; Chih-Da Wu (Theoretical and Applied Climatology, 2020)

Numerical Investigation of NOx Emission Reduction in Non-Premixed Lean Reverse-Flow Combustor in a Micro Gas Turbine Engine - Jesline Joy; Peng Cheng Wang; Jeggathishwaran Panisilvam; Simon Ching Man Yu (Emission Control Science and Technology, 2020)

Pulse Oximetry Monitor Feasible for Early Screening of Obstructive Sleep Apnea (OSA) - Huei-Chen Lin; Chien-Ling Su; Jun-Hui Ong; kun-ling Tsai; Yu-Wen Chen; Cheng-Yu Lin; Ling-Ling Chiang; Ching-Hsia Hung (Journal of Medical and Biological Engineering, 2020)

In vitro activities of imipenem, vancomycin, and rifampicin against clinical Elizabethkingia species producing BlaB and GOB metallo-beta-lactamases - Tein-Yao Chang; Hsing-Yu Chen; Yu-Ching Chou; Yun-Hsiang Cheng; Jun-Ren Sun (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

LpxD gene knockout elicits protection to Litopenaeus vannamei, white shrimp, against Vibrio parahaemolyticus infection - Ching-Yi Tsai; Harvey M. Santos; Shao-Yang Hu; Cheng Yu Sang; Ciara Alyssa S. Yanuaria; Ernest Nicolo G. Lola; Lemmuel L. Tayo; Karmella Marie A. Nitura; Chun Hung Liu; Kuo Pin Chuang (Aquaculture International, 2019)

Prevalence of mycotoxins in feed and feed ingredients between 2015 and 2017 in Taiwan - Ching-Kuo Yang; Yeong-Hsiang Cheng; Wan-Ting Tsai; Rou-Wan Liao; Chia-Sheng Chang; Wan-Chu Chien; Jia-Cin Jhang; Yu-Hsiang Yu (Environmental Science and Pollution Research, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Magnesium sulfate inhibits binding of lipopolysaccharide to THP-1 cells by reducing expression of cluster of differentiation 14 - Ya-Ying Chang; Tzu-Yu Lin; Ming-Chang Kao; Tsung-Ying Chen; Ching-Feng Cheng; Chih-Shung Wong; Chun-Jen Huang (Inflammopharmacology, 2019)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

Effects of normoxic and hypoxic exercise training on the bactericidal capacity and subsequent apoptosis of neutrophils in sedentary men - Yi-Ching Chen; Wan-Yu Chou; Tieh-Cheng Fu; Jong-Shyan Wang (European Journal of Applied Physiology, 2018)

Protein-bounded uremic toxin p-cresylsulfate induces vascular permeability alternations - Wei-Hua Tang; Chao-Ping Wang; Teng-Hung Yu; Pei-Yang Tai; Shih-Shin Liang; Wei-Chin Hung; Cheng-Ching Wu; Sung-Hao Huang; Yau-Jiunn Lee; Shih-Chieh Chen (Histochemistry and Cell Biology, 2018)

Epirubicin induces apoptosis in osteoblasts through death-receptor and mitochondrial pathways - Tzu-Ching Huang; Pu-Rong Chiu; Wen-Tsan Chang; Bau-Shan Hsieh; Yu-Ci Huang; Hsiao-Ling Cheng; Li-Wen Huang; Yu-Chen Hu; Kee-Lung Chang (Apoptosis, 2018)

Chemical Characteristics of Different Tissues of Spectacled Caiman ( Caiman crocodilus ) - Yu-Ru Huang; Yung-Hsiang Tsai; Ching-Lu Liu; Wei-Zong Syue; Yi-Cheng Su (Journal of Aquatic Food Product Technology, 2018)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

Status quo of management of the human tissue banks in Taiwan - Ching-Pang Chou; Szu-Cheng Chou; Ying-Hua Chen; Yu-Hsuan Chen; Ming-Shin Lee (Cell and Tissue Banking, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

Caffeine ingestion improves power output decrement during 3-min all-out exercise - Ching-Feng Cheng; Wei-Chieh Hsu; Yu-Hsuan Kuo; Ming-Tsung Shih; Chia-Lun Lee (European Journal of Applied Physiology, 2016)

A galactopoiesis accordant yield of functional recombinant human factor IX from homozygous transgenic pigs requires a large amount of vitamin K supplementation - Chon-Ho Yen; Tien-Shuh Yang; Yin-Shen Lin; Meng-Hwan Lee; Kuo-Cheng Yu; Chung-Lin Huang; How-Hong Hsieh; Ching-Fu Tu (Transgenic Research, 2016)

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells - Chun-Liang Tung; Yi-Jun Jian; Jyh-Cheng Chen; Tai-Jing Wang; Wen-Ching Chen; Hao-Yu Zheng; Po-Yuan Chang; Kai-Sheng Liao; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Associations between TRPV4 genotypes and body mass index in Taiwanese subjects - De-Min Duan; Semon Wu; Lung-An Hsu; Ming-Sheng Teng; Jeng-Feng Lin; Yu-Chen Sun; Ching-Feng Cheng; Yu-Lin Ko (Molecular Genetics and Genomics, 2015)

Identification and quantification of Cu-chlorophyll adulteration of edible oils - Mingchih Fang; Chia-Fen Tsai; Guan-Yan Wu; Su-Hsiang Tseng; Hwei-Fang Cheng; Ching-Hao Kuo; Che-Lun Hsu; Ya-Min Kao; Daniel Yang-Chih Shih; Yu-Mei Chiang (Food Additives & Contaminants Part B-Surveillance, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

The Akt inhibitor MK-2206 enhances the cytotoxicity of paclitaxel (Taxol) and cisplatin in ovarian cancer cells - Ying-Hsi Lin; Bert Yu-Hung Chen; Wei-Ting Lai; Shao-Fu Wu; Jih-Hwa Guh; Ann-Lii Cheng; Lih-Ching Hsu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity - Yun-Ping Lim; Ching-Hao Cheng; Wei-Cheng Chen; Shih-Yu Chang; Dong-Zong Hung; Jih-Jung Chen; Lei Wan; Wei-Chih Ma; Yu-Hsien Lin; Cing-Yu Chen; Tsuyoshi Yokoi; Miki Nakajima; et al. (Archives of Toxicology, 2015)

Co-ingestion of caffeine and carbohydrate after meal does not improve performance at high-intensity intermittent sprints with short recovery times - Chia-Lun Lee; Ching-Feng Cheng; Chia-Jung Lee; Yu-Hsuan Kuo; Wen-Dien Chang (European Journal of Applied Physiology, 2014)

Maintenance of human adipose derived stem cell (hASC) differentiation capabilities using a 3D culture - Ching-Yu Lin; Chi-Hui Huang; Yuan-Kun Wu; Nai-Chen Cheng; Jiashing Yu (Biotechnology Letters, 2014)

Minocycline accelerates hypoxia-inducible factor-1 alpha degradation and inhibits hypoxia-induced neovasculogenesis through prolyl hydroxylase, von Hippel–Lindau-dependent pathway - Ching-Hao Li; Po-Lin Liao; Ya-Ting Yang; Shih-Hsuan Huang; Cheng-Hui Lin; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2013)

Design, synthesis, and evaluation of fluorescent cell-penetrating peptidic antagonists of Grb2-SH2 for targeting MCF-7 breast cancer cells - Yu-Cheng Hsiao; Chen-Yu Lee; Yi-Jhen Lin; Shu-Huai Tsai; Kee-Ching G. Jeng; Wei-Ting Chao; Feng-Di T. Lung (Medicinal Chemistry Research, 2013)

Hyperinakin, a new anti-inflammatory phloroglucinol derivative from Hypericum nakamurai - Yuan-Bin Cheng; Ahmed Eid Fazary; Yu-Chi Lin; I-Wen Lo; Seow-Chin Ong; Shun-Ying Chen; Ching-Te Chien; Yen-Jung Lin; Wan-Wan Lin; Ya-Ching Shen (Natural Product Research, 2013)

Composition and Distribution of Elements and Ultrastructural Topography of a Human Cardiac Calculus - Ching-Li Cheng; Hsiao-Huang Chang; Pei-Jung Huang; Yu-Ting Chu; Shan-Yang Lin (Biological Trace Element Research, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

Recombined sequences between the non-coding control regions of JC and BK viruses found in the urine of a renal transplantation patient - Yu-Ching Liaw; Cheng-Hsu Chen; Kuo-Hsiung Shu; Chiung-Yao Fang; Wei-Chih Ou; Pei-Lain Chen; Cheng-Huang Shen; Mien-Chun Lin; Deching Chang; Meilin Wang (Virus Genes, 2012)

Interplay of RsbM and RsbK controls the σ B activity of Bacillus cereus - Lei‐Chin Chen; Jung‐Chi Chen; Jwu‐Ching Shu; Chien‐Yen Chen; Ssu‐Ching Chen; Shu‐Hwa Chen; Chun‐Yen Lin; Chi‐Yu Lu; Chien‐Cheng Chen (Environmental Microbiology, 2012)
Summary The alternative transcription factor σ B of Bacillus cereus controls the expression of a number of genes that respond to environmental stress. Four proteins encoded in the sigB gene cluster, including RsbV, RsbW, RsbY (RsbU) and RsbK, are known to be essential in the σ B ‐mediated stress response. In the context of stress, the hybrid sensor kinase RsbK is thought to phosphorylate the response regulator RsbY, a PP2C serine phosphatase, leading to the dephosphorylation of the phosphorylated RsbV. The unphosphorylated RsbV then sequesters the σ B antagonist, RsbW, ultimately liberating σ B . The gene arrangement reveals an open reading frame, bc1007 , flanked immediately downstream by rsbK within the sigB gene cluster. However, little is known about the function of bc1007 . In this study, the deletion of bc1007 resulted in high constitutive σ B expression independent of environmental stimuli, indicating that bc1007 plays a role in σ B regulation. A bacterial two‐hybrid analysis demonstrated that BC1007 interacts directly with RsbK, and autoradiographic studies revealed a specific C 14 ‐methyl transfer from the radiolabelled S‐adenosylmethionine to RsbK when RsbK was incubated with purified BC1007. Our data suggest that BC1007 (RsbM) negatively regulates σ B activity by methylating RsbK. Additionally, mutagenic substitution was employed to modify 12 predicted methylation residues in RsbK. Certain RsbK mutants were able to rescue σ B activation in a rsbK ‐deleted bacterial strain, but RsbK E439A failed to activate σ B , and RsbK E446A only moderately induced σ B . These results suggest that Glu439 is the preferred methylation site and that Glu446 is potentially a minor methylation site. Gene arrays of the rsbK orthologues and the neighbouring rsbM orthologues are found in a wide range of bacteria. The regulation of sigma factors through metylation of RsbK‐like sensor kinases appears to be widespread in the microbial world.

Induction of primitive pigment cell differentiation by visible light (helium–neon laser): a photoacceptor-specific response not replicable by UVB irradiation - Cheng-Che E. Lan; Shi-Bei Wu; Ching-Shuang Wu; Yi-Chun Shen; Tzu-Ying Chiang; Yau-Huei Wei; Hsin-Su Yu (Journal of Molecular Medicine, 2012)

Characterization and prediction of mRNA polyadenylation sites in human genes - Tzu-Hao Chang; Li-Ching Wu; Yu-Ting Chen; Hsien-Da Huang; Baw-Jhiune Liu; Kuang-Fu Cheng; Jorng-Tzong Horng (Medical & Biological Engineering & Computing, 2011)

Role of DNA methyltransferase 1 in hormone-resistant prostate cancer - Miao-Fen Chen; Wen-Cheng Chen; Yu-Jia Chang; Ching-Fang Wu; Chun-Te Wu (Journal of Molecular Medicine, 2010)

A novel mutation in the connexin 29 gene may contribute to nonsyndromic hearing loss - Hui-Mei Hong; Jiann-Jou Yang; Ching-Chyuan Su; Juan-Yu Chang; Tung-Cheng Li; Shuan-Yow Li (Human Genetics, 2010)

NaCl-induced expression of glutathione reductase in roots of rice (Oryza sativa L.) seedlings is mediated through hydrogen peroxide but not abscisic acid - Chwan-Yang Hong; Yun-Yang Chao; Min-Yu Yang; Sin-Yuan Cheng; Shih-Chueh Cho; Ching Huei Kao (Plant and Soil, 2009)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Estimating the economic impacts of climate change on infectious diseases: a case study on dengue fever in Taiwan - Wei-Chun Tseng; Chi-Chung Chen; Ching-Cheng Chang; Yu-Hsien Chu (Climatic Change, 2009)

Time to rehospitalization in patients with bipolar I disorder on lithium or valproate with adjunctive antipsychotics - Ching-Hua Lin; Ching-Wen Huang; Cheng-Chung Chen; Yu-Fen Hsu; Wen-Ho Chang; Hsien-Yuan Lane (Psychopharmacology, 2008)

Subunit fusion of two yeast d-amino acid oxidases enhances their thermostability and resistance to H2O2 - Shih-Juei Wang; Chi-Yang Yu; Cheng-Kang Lee; Ming-Kai Chern; I-Ching Kuan (Biotechnology Letters, 2008)

Gene expression variation increase in trisomy 21 tissues - Ching Yu Chou; Li Yu Liu; Chien Yu Chen; Cheng Hsien Tsai; Hsiao Lin Hwa; Li Yun Chang; Yi Shing Lin; Fon Jou Hsieh (Mammalian Genome, 2008)

Two new xeniolides from a Taiwanese Xenia soft coral - Ya-Ching Shen; Yu-Hui Chen; Yuan-Bin Cheng; Yao Haur Kuo; Ashraf Taha Khalil (Natural Product Research, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Production of high-content galacto-oligosaccharide by enzyme catalysis and fermentation with Kluyveromyces marxianus - Chao-Chun Cheng; Mei-Ching Yu; Tzu-Chien Cheng; Dey-Chyi Sheu; Kow-Jen Duan; Wei-Lun Tai (Biotechnology Letters, 2006)

Production of High-content Galacto-oligosaccharide by Enzyme Catalysis and Fermentation with Kluyveromyces marxianus - Chao-Chun Cheng; Mei-Ching Yu; Tzu-Chien Cheng; Dey-Chyi Sheu; Kow-Jen Duan; Wei-Lun Tai (Biotechnology Letters, 2006)

Contrasting phylogeographical patterns of two closely related species, Machilus thunbergii and Machilus kusanoi (Lauraceae), in Taiwan - Su‐Hwa Wu; Ching‐Yuan Hwang; Tsan‐Piao Lin; Jeng‐Der Chung; Yu‐Pin Cheng; Shih‐Ying Hwang (Journal of Biogeography, 2006)
Aim The purpose of this paper was to study the patterns of genetic variation, demographic history, haplotype relationships and potential location of diversity centres of two closely related species, Machilus thunbergii and Machilus kusanoi . Location The phylogeography of M. thunbergii and M. kusanoi was examined by sampling 110 and 106 individuals from 25 and 16 sampling sites, respectively, across their distributional range in Taiwan. Machilus thunbergii is distributed on the Asian mainland, South Korea, southern Japan, the Ryukyus, Taiwan and the Philippines, whereas M. kusanoi is endemic to Taiwan. These two species are closely related, and both are widely distributed in Taiwan but occupy different altitudinal zones and habitats. Methods The range‐wide variation of M. thunbergii and M. kusanoi in Taiwan was studied using chloroplast DNA (cpDNA) variations. A haplotype network was constructed with the computer program tcs . Nested clade analysis was conducted with the computer program ceodis , and various parameters of genetic diversity were calculated and neutrality tested by the computer program D na SP. Population differentiation was estimated using the programs arlequin and hapstep . The contribution of the populations to gene diversity and to allelic richness was calculated using the software contrib . The level of divergence for each population from the remaining populations was calculated as the mean value of pairwise F ST for each population against the rest of the populations. Results Extremely low levels of genetic differentiation were found for both species. This result suggested that these two species probably survived in multiple relict refugia with different population sizes throughout the island during low‐temperature periods of the Pleistocene. In addition, nested clade analysis (NCA) of cpDNA haplotypes indicated that restricted gene flow with isolation‐by‐distance characterized the recolonization after the Pleistocene by Tashueshan and Shiouhluan populations of M. thunbergii in the north‐central area west of the Central Mountain Range (CMR). In contrast, NCA analysis indicated that a major diversity centre on the southern tip of the island (Kending population) and contiguous range expansion characterized the recolonization by M. kusanoi of northern areas along the east side of the CMR. The major diversity centres found for the two species examined were further supported by the results of the mean F ST for individual populations in comparison with other populations, and of the contribution of the divergence component to the total diversity. Main conclusions This research supports the multiple relict refugia hypothesis for both species investigated. Populations of M. thunbergii at Shiouhluan and Tashueshan in the north‐central area west of the CMR represent a diversity centre currently expanding its size. A diversity centre at the southern‐edge population of M. kusanoi , and a contiguous range expansion from Kending, were found. These results indicate that the M. thunbergii populations at Tashueshan and Shiouhluan and the M. kusanoi population at Kending, and even Soukar, are evolutionarily significant units for conservation programmes.

Transgenic tomato plants expressing the Arabidopsis NPR1 gene display enhanced resistance to a spectrum of fungal and bacterial diseases - Wan-Chi Lin; Ching-Fang Lu; Jia-Wei Wu; Ming-Lung Cheng; Yu-Mei Lin; Ning-Sun Yang; Lowell Black; Sylvia K. Green; Jaw-Fen Wang; Chiu-Ping Cheng (Transgenic Research, 2004)

Alpha-naphthoflavone induces vasorelaxation through the induction of extracellular calcium influx and NO formation in endothelium - Yu-Wen Cheng; Ching-Hao Li; Chen-Chen Lee; Jaw-Jou Kang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Cloning and characterization of murine Fanconi anemia group A gene: Fanca protein is expressed in lymphoid tissues, testis, and ovary - Henri J. van de Vrugt; Ngan Ching Cheng; Yne de Vries; Martin A. Rooimans; Jan de Groot; Rik J. Scheper; Yu Zhi; Maureen E. Hoatlin; Hans Joenje; Fré Arwert (Mammalian Genome, 2000)